MC38 colorectal tumor cell lines from two different sources display substantial differences in transcriptome, mutanome and neoantigen expression - Schrörs, Barbara; Hos, Brett J.; Yildiz, Ikra G.; Löwer, Martin; Lang, Franziska; Holtsträter, Christoph; Becker, Julia; Vormehr, Mathias; Sahin, Ugur; Ossendorp, Ferry; Diken, Mustafa (Frontiers in Immunology, 2023)
The cell line MC38 is a commonly used murine model for colorectal carcinoma. It has a high mutational burden, is sensitive to immune checkpoint immunotherapy and endogenous CD8+ T cell responses against neoantigens have been reported. Here, we re-sequenced exomes and transcriptomes of MC38 cells from two different sources, namely Kerafast (originating from NCI/NIH) and the Leiden University Medical Center cell line collection, comparing the cell lines on the genomic and transcriptomic level and analyzing their recognition by CD8+ T cells with known neo-epitope specificity. The data reveals a distinct structural composition of the Kerafast and Leiden cell line genomes and different ploidies. Further, the Leiden cell line harbored about 1.3-fold more single nucleotide variations and small insertions and deletions than the Kerafast cell line. In addition, the observed mutational signatures differed; only 35.3% of the non-synonymous variants and 5.4% of the fusion gene events were shared. Transcript expression values of both cell lines correlated strongly (p = 0.919), but we found different pathways enriched in the genes that were differentially upregulated in the Leiden or Kerafast cells, respectively. Our data show that previously described neoantigens in the MC38 model such as Rpl18mut and Adpgkmut were absent in the Kerafast cell line resulting that such neoantigen-specific CD8+ T cells recognizing and killing Leiden cells did not recognize or kill Kerafast cells. This strongly indicates that at least two sub-cell lines of MC38 exist in the field and underlines the importance of meticulous tracking of investigated cell lines to obtain reproducible results, and for correct interpretation of the immunological data without artifacts. We present our analyses as a reference for researchers to select the appropriate sub-cell line for their own studies.